2003
DOI: 10.3346/jkms.2003.18.5.641
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and Enalapril attenuate the Development of Right Ventricular Hypertrophy induced by Monocrotaline in Ovariectomized Rats

Abstract: INTRODUCTIONGender differences in the development of cardiovascular diseases have been documented in both human and animal studies. The rate of incidence of cardiovascular disease is lower in premenopausal women than in men, but increases sharply in postmenopausal women (1). Among the clinical consequences of postmenopausal estrogen deficiency, the deaths associated with cardiovascular diseases represent the largest concern in public health. Many studies have demonstrated that estrogen replacement therapy redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 36 publications
1
33
0
Order By: Relevance
“…In the present study, we used MCT-induced RVH in rat to probe the possible inhibitory effect of Rb 1 on cardiac hypertrophy, because it has been well known that MCT is converted in the liver to MCT-pyrrole which causes injury of the lung vasculature and leads to pulmonary hypertension and RVH (Chen et al, 2001;Ahn et al, 2003). In MCT-treated animals, the significant increase in LW/BW, RVHI, and RV/BW, the electron microscopic findings of RV, and the elevation of ANP expression (a fetal heart marker protein) strongly suggested that there existed the formation of pulmonary hypertension and RVH, which meant that the establishment of RVH model in our experiment was successful.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we used MCT-induced RVH in rat to probe the possible inhibitory effect of Rb 1 on cardiac hypertrophy, because it has been well known that MCT is converted in the liver to MCT-pyrrole which causes injury of the lung vasculature and leads to pulmonary hypertension and RVH (Chen et al, 2001;Ahn et al, 2003). In MCT-treated animals, the significant increase in LW/BW, RVHI, and RV/BW, the electron microscopic findings of RV, and the elevation of ANP expression (a fetal heart marker protein) strongly suggested that there existed the formation of pulmonary hypertension and RVH, which meant that the establishment of RVH model in our experiment was successful.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of mice with deletion of the endothelial nitric oxide synthase gene, structural evidence of pulmonary hypertension was evident in male but not in female adult mice. 29 Further investigation of gender differences in the expression of the PAH phenotype in VIP Ϫ/Ϫ mice and of the possible role of estrogen in such differences 30,31 is clearly in order. A predominant expression of the pulmonary vascular abnormalities in male VIP Ϫ/Ϫ mice, if confirmed, would be clearly different from human IPAH, which is more prevalent in women.…”
Section: Discussionmentioning
confidence: 99%
“…16,17) In the present study, we used MCT-induced RVH in rat to examine the possible inhibitory effect of TG on cardiac hypertrophy. In MCT-treated animals, the increase in RVPSP and the findings in the electron microscopic observation strongly indicated that there existed the formation of pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%